A Pengaruh Kualitas Pelayanan Farmasi Terhadap Kepuasan Pasien Rawat Jalan Di RS Hermina Tangkubanprahu Malang - Khusnul Khotimah; Rahayu Ningsih (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Quality of pharmaceutical services is one of the indicators used to assess patient satisfaction.The aim of this study was to assess the quality of pharmaceutical services, patient satisfaction, and the relationship between the quality of pharmaceutical services and patient satisfaction. The main benefit of this research is information regarding the quality of pharmaceutical services and patient satisfaction. Non-experimental observational research is the research method. Data were obtained from outpatient questionnaires at Hermina Hospital.The SERVQUAL method was used for the assessment of service quality with 15 questions for each patient's perception and expectation value. Patient satisfaction was assessed with a questionnaire of 21 questions. The validity and reliability of the questionnaire has been tested. Descriptive statistical analysis and Spearman Rank correlation test were used for data analysis. A sample of 97 respondents, 45 males (46%) and 52 females (54%). Was obtained The majority of respondents were private sector employees (n=30;31%). Average monthly income < 3 million (n=51; 53%). The majority of visits to Hermina Hospital were 2-5 times (n=41; 42%). The service quality score was 3.27 on scale of 1-4 and the patient satisfaction score was 3.11. Correlation test results showed a significance value of p = 0.000 and a correlation coefficient = 0.660. This study concludes that the quality of pharmaceutical services is in the good category (81.75%), patient satisfaction is in the satisfied category (77.75%), and there is a significant influence (p=0.000) between the quality of pharmaceutical services and the satisfaction of Hermina Hospital outpatients. Tangkubanprahu Malang